METODE DAKWAH SUNAN KALIJAGA DALAM PROSES ISLAMISASI DI JAWA - Solikin Solikin; Syaiful M; Wakidi Wakidi (FKIP UNIVERSITAS LAMPUNG, 2013)
The era of Wali Songo is the end of domination Hindu-Budhist Era in cultural heritage to be replaced with Islamic culture. But the Role of Wali Songo heavily in establishing the Islamic kingdom in java, as well as their influence on the culture of society largely and religious proselytizing directly, making the figures more widely known than any other characters Islamic missionaries. Among the members of the Wali Songo whose name is very popular by people in the java is Sunan Kalijaga or Raden Syahid. He was one of the most influential figures in the process of Islamization in Java. Tolerant to local culture and utilization of the world of art and culture became his charactristic in religious proselytizing of method. Puppets, gamelan, mysticism or any other traditional song and culture are part of the culture of Javanese society which succesfully utilized as means of religious proselytizing by sunan kalijaga. Based on the studying above, the research question in this research is how the method is applied Sunan Kalijaga mission through a cultural approach in the process of Islamization of Java.Keywords : metode dakwah, Islamisasi di Jawa